Malagasy traditional treatments for food crops: A tool to control potato bacterial diseases?. (December 2017) - Rasamiravaka, Tsiry; Rajaonarivelo, Jacob Philémon; Rabemanantsoa, Christian; El Jaziri, Mondher; Andrianarisoa, Blandine; Duez, Pierre
Abstract: The control and treatment of food crops bacterial diseases remain problematic due to a scarcity of effective phytotreatments. As traditional agricultural practices may represent an attractive venue to explore new treatments, Malagasy traditional practices were investigated for their effectiveness on potato plants. A survey was conducted among Malagasy farmers to collect information on diseases observed on potato crops and on traditional disease control practices. Twelve treatments against potato bacterial diseases were tested on two potato varieties, in experimental plots naturally infected by bacterial wilt disease. The information collected from 52 farmers (i) showed that leaf spots and bacterial wilt disease are the most frequently identified threats for potato crops; and (ii) allowed to identify 12 traditional treatments among which five exhibited protective properties on potato bacterial wilt disease. Moreover, one recipe (R07) was effective on the two potato varieties after two applications per week for 10 weeks, with 50% and 72% effectiveness rate, respectively. Valorization of traditional practices may provide an effective, safe, economic and standardized phytotreatment against potato bacterial wilt disease. Graphical abstract: Highlights: Identification of 54 traditional recipes used by Malagasy farmers. Most of recipes consist of complex mixtures, often fermented with cow dungs. Five traditional recipes exhibit healing properties on potato bacterial wilt disease. Traditional practices may provide an effective and economic phytotreatment.